2004
DOI: 10.1021/jp047546i
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for the Destruction of CFC-12 in a Nonthermal, Atmospheric Pressure Plasma

Abstract: The destruction of CFC-12 (CF2Cl2) has been studied in an AC, nonthermal, atmospheric pressure plasma reactor packed with barium titanate beads. The extent of the destruction in air ranges between 8% and 40% depending on the conditions. The decomposition products in air as determined by infrared spectroscopy are CO, CO2, and COF2. It is deduced that the undetected chlorine and fluorine is present as F2 and Cl2. A chemical mechanism for the decomposition is proposed. Large concentrations of NO, NO2, and N2O are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…However, the product selectivity also depends on the water content in addition to VOC chemical structure. Some studies reported the optimal water vapor content for achieving the best VOC removal efficiency (Ricketts et al 2004;Sugasawa et al 2010: Karuppiah et al 2012). The effect of water vapor has been mostly studied with packed-bed DBD reactors for removal of benzene (Ogata et al 2000;Cal and Schluep 2001;Futamura et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…However, the product selectivity also depends on the water content in addition to VOC chemical structure. Some studies reported the optimal water vapor content for achieving the best VOC removal efficiency (Ricketts et al 2004;Sugasawa et al 2010: Karuppiah et al 2012). The effect of water vapor has been mostly studied with packed-bed DBD reactors for removal of benzene (Ogata et al 2000;Cal and Schluep 2001;Futamura et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Particularly high temperatures (~1250 °C) are needed to ensure that the halogenated components are safely destroyed without the formation of dioxins. We previously studied the destruction of dichlorodifluoromethane, CCl 2 F 2 , (CFC-12) in an air stream using only a plasma discharge [8]. By incorporating a range of catalysts into the plasma discharge in a one-stage configuration, we could significantly increase the destruction of the CFC-12 as is shown in Fig.…”
Section: Destruction Of Cfc-12 Using Plasma Catalysismentioning
confidence: 99%
“…In these experiments, we again use a dielectric, barium titanate, packed-bed plasma reactor which can be heated up to 400 °C. The catalysts are combined with the plasma whose input power is 1 W, which is determined by integration of the current and voltage waveforms with a typical precision of ±10 % [8].…”
Section: Temperature Dependence Of Plasma-assisted Catalysismentioning
confidence: 99%
“…It should be noted that NO involved in reactions (19) and (20) is formed by the reaction between excited atomic nitrogen N( 2 D) and O 2 (Ricketts et al, 2004;Harling et al, 2005 …”
Section: Destruction Pathways 221 Trifluoromethanementioning
confidence: 99%